2012
DOI: 10.5367/te.2012.0141
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Seasonal Price Patterns among Second Home Rentals and Hotels: Empirical Evidence and Practical Implications

Abstract: Hotels and second home rentals are two of the most important tourist accommodation options in Spain. In terms of seasonality, almost all previous studies have analysed tourism demand from the point of view either of total arrivals or the number of tourists lodged in a single accommodation type (hotels, rural accommodation, etc). However, there are no studies focusing on price seasonality or comparing seasonality among different accommodation types. By using seasonality indicators and a price index constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…This is because a supply curve, as a relationship that determines the amount supplied for each price, cannot be built for imperfect competitive markets where short-run competition among suppliers is realized through prices, as is the case for hotels (Lee and Jang 2013). Now, it is common in the empirical literature on hotels' seasonality in prices to model price setting using an hedonic price function (Espinet et al 2012;Juaneda, Raya, and Sastre 2011;Saló et al 2012) fed by individual data on hotel prices and characteristics. However, given the level of aggregation of our database, this approach seems inadequate.…”
Section: The Price-setting Schedulementioning
confidence: 99%
See 1 more Smart Citation
“…This is because a supply curve, as a relationship that determines the amount supplied for each price, cannot be built for imperfect competitive markets where short-run competition among suppliers is realized through prices, as is the case for hotels (Lee and Jang 2013). Now, it is common in the empirical literature on hotels' seasonality in prices to model price setting using an hedonic price function (Espinet et al 2012;Juaneda, Raya, and Sastre 2011;Saló et al 2012) fed by individual data on hotel prices and characteristics. However, given the level of aggregation of our database, this approach seems inadequate.…”
Section: The Price-setting Schedulementioning
confidence: 99%
“…A scarcer branch of the research area analyzes seasonality in prices. Two articles compare price seasonality in hotels to price seasonality in apartments (Juaneda, Raya, and Sastre 2011) and in home rentals (Saló et al 2012). Three additional articles delve into the determinants of hotel price seasonality (Coenders, Espinet, and Saez 2003;Espinet et al 2012;Wang, Sun, and Wen 2019), finding that characteristics of both hotels and destinations are explanatory of differences in the seasonality of hotel prices.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the hedonic method has been widely used in valuing goods and services that cannot be priced directly via market transactions (Zygmunt & Gluszak, 2015). However, most of the studies are focused on price-making for an individual recreation site or activity, for example, price-making for a specific recreational resort and a designed holiday package (Alegre et al, 2013), second home (Saló et al, 2012), a restaurant (Yim et al, 2014) and a hotel room (Schamel, 2012). Certainly, when tourists encounter more inconveniences and/or unpleasant experiences caused by dirty surroundings and crowding conditions, etc., they must result in negative effect on related coastal park admission fee charges, thus causing the park's revenue losses (Taylor, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This contrasts with our Danish case where second homeownership is slightly more common among households in detached single-family dwellings. Two papers by Salo and Garriga (2011) and Salo et al (2012) study the pricing of second home rentals and hotels in the Costa Brava region. Salo and Garriga (2011) use the weekly price for second home rentals as dependent variable and demonstrate how this variable varies with the number of rooms, the size in square meters, the distance to the beach, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also shown that wholesalers are able to charge a higher price than direct or retail sellers. In Salo et al (2012) it is shown that prices for second home rentals display a smoother seasonal pattern than hotel prices for a week's stay. Belsky et al (2007) use data from the 1995 American Housing Survey and the 2004 Survey of Consumer Finances to model second home demand and the permanent income elasticity of housing demand.…”
Section: Literature Reviewmentioning
confidence: 99%